Prophet, Priest, and King : Christology in global perspective - Horton, Michael Scott; Mburu, Elizabeth W., 1968-; Holcomb, Justin S., 1973- (Grand Rapids, Michigan : Zondervan Academic, 2025)
"Written by a global team of leading Majority World scholars, this volume approaches, explores, and articulates the topic of Christology and the Gospel, not only as central and essential tenets of the Christian faith but also as the global, catholic church"--
"An exploration of the doctrine of Christ from the global church for the global church.Written by a global team of leading Majority World scholars led by Michael S. Horton, Elizabeth W. Mburu, and Justin S. Holcomb, Prophet, Priest, and King approaches, explores, and articulates the topic of Christology and the Gospel, not only as central and essential tenets of the Christian faith but crucially as the global, Catholic Church.Though there are many global treatments of Christology that focus on contextual expression, and many more written from a Western perspective, Prophet, Priest, and King deliberately and uniquely highlights a unified and singular testimony drawn from a variety of voices from the worldwide church. Thus, rather than attempting to articulate various contextual theologies and each of their distinctives, Prophet, Priest, and King explores and expresses the one, Catholic, and Apostolic Christian faith amongst various ecclesiological and global perspectives"--
the curch as Christ's prophetess / Wilson Jeremiah -- More than a prophet: Arb Christians and the question of Christology / Wageeh Mikhail.
Includes bibliographical references and indexes.
Description based on print version record and CIP data provided by publisher.
Keywords: Jesus Christ -- Person and offices; RELIGION / Christian Theology / Christology; RELIGION / Biblical Studies / New Testament / Jesus, the Gospels & Acts